Bottom-up processes drive reproductive success of Japanese anchovy in an oligotrophic sea: A case study in the central Seto Inland Sea, Japan - Yoneda, Michio; Fujita, Tatsunori; Yamamoto, Masayuki; Tadokoro, Kazuaki; Okazaki, Yuji; Nakamura, Masahiro; Takahashi, Masanori; Kono, Naoaki; Matsubara, Tadashi; Abo, Katsuyuki; Xinyu, Guo; Yoshie, Naoki (Progress in oceanography, 2022)
•Community structure of copepod species changed over the 19-year study period.•Biomass of cool-water copepod species markedly decreased in the last decade.•Elevated temperature and declining chlorophyll a levels were recently observed.•Condition factor of females and egg size of anchovy decreased over the period.•Maternal prey availability of anchovy significantly affected offspring viability. Anthropogenic and/or climate-driven changes in zooplankton dynamics may serve as a bottom-up regulator of productivity of small pelagic fish. In the central Seto Inland Sea of Japan, the abundance of the recruit fish of Japanese anchovy (Engraulis japonicus) has markedly declined in the last decade under oligotrophication. However, the link between the reproductive success of anchovy and environmental variation is largely unclear. This study explored the potential association between changes in the zooplankton (copepods) community structure and the reproductive condition of anchovy in this oligotrophic sea using survey data from spring to summer of 2001–2019. The community structure of copepod species changed markedly in May–July, covering the main spawning season of anchovy, as decreases in the biomass of several copepods found in cooler water in a given season (May–June) were observed. Although relationships between chlorophyll a concentrations and the copepod biomass were unclear, the recent decline of their cooler-water copepods may be attributed to the influences of elevated sea surface temperature and decreasing levels of chlorophyll a. The latter may be associated with decreasing nitrogen levels. Among these species, Calanus sinicus and Corycaeus affinis could be important prey items for anchovy from the analyses of prey selectivity and relationships between the relative condition factor of females and the copepod biomass. The egg size–temperature relationships of anchovy appeared to be associated with the relative condition factor of females and survival rates in the early stage of life, suggesting that females with a poor body condition produced smaller eggs in recent years. Maternal food manipulation experiments supported the assumption that larvae born to females fed a restricted food ration exhibited lower starvation tolerance and slower growth than born to females provided feed ad libitum. These findings suggest that the reproductive success of anchovy could be subject to bottom-up trophic drivers mediated by maternal contributions to offspring viability, and this partly explains why the level of anchovy recruitment has rapidly declined in the last decade.